Biological traits of Ascogaster quadridentata an endoparasitoid of the codling moth - Hernandez, Carmen Marcela (2022)
The developmental time, adult longevity, survival, and fecundity of Ascogaster quadridentata reared on Cydia pomonella were studied at 25 ± 2 ºC and natural lighting. Longevity was measured in different conditions: water; water and honey; and water, honey and host. Developmental time from egg to adult was 43.67 ± 0.75 days. Honey had a significant effect on the longevity of female adults. The longevity of females with water was 3 days, whereas females fed with honey had longevity values greater than 6 days. The survival curves of adults fed with honey and adults starved were different. All males with water died before 5 days; while in honey-fed males, the last adult died on days 16 and 22, with and without a host, respectively. The female began ovipositing eggs during the first days following emergence. A female produced on average, 22.3 ± 4.7 eggs/day, and more than 10% of host eggs were superparasitized. The parasitism rate was on average 17.53 ± 2.88 hosts/day, whereas the total mean parasitism was 202.75 ± 59.24 hosts/female. This study addressed new basic biological information about A. quadridentata and contribute to a better understanding of its potential as a biological control agent of codling moth.